2016
DOI: 10.1007/s13224-015-0826-2
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Aneuploidy Screen and Adverse Pregnancy Outcomes

Abstract: Objective To find out whether maternal serum screening for fetal chromosomal aneuploidy predicts adverse pregnancy outcomes. Methods A two-year retrospective case-control study was conducted at a tertiary hospital. Pregnant women with a high-risk serum screen but with chromosomally normal fetuses (n = 189) were compared to those with low-risk screen (controls, n = 157) for adverse pregnancy outcomes. p \ 0.005) and gestational age (R 2 = 4.9 %, b ± SE = 0.613 ± 0.296; p \ 0.05). Beta hCG in first and hCG in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…An increased risk of pregnancy complications, such as pre-eclampsia, stillbirth, preterm birth and SGA, has been found previously after a false-positive high-risk result on first-and second-trimester aneuploidy screening [8][9][10][11][12] . The findings of our study extend this association to women with a false-positive high or intermediate risk for aneuploidy and suggest that, in these women, further screening for SGA may increase the detection rate of fetal-growth disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased risk of pregnancy complications, such as pre-eclampsia, stillbirth, preterm birth and SGA, has been found previously after a false-positive high-risk result on first-and second-trimester aneuploidy screening [8][9][10][11][12] . The findings of our study extend this association to women with a false-positive high or intermediate risk for aneuploidy and suggest that, in these women, further screening for SGA may increase the detection rate of fetal-growth disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, advanced maternal age (≥ 35 years at the time of delivery) is associated not only with an increased risk of fetal chromosomal abnormality 25 , but is also reported invariably as an independent risk factor for SGA/FGR [26][27][28] . While elevated levels of free β-hCG have not been found to be associated with delivery of a SGA neonate 29,30 , low PAPP-A level has been described widely in connection with a broad range of adverse perinatal outcomes including SGA 9,10,31,32 . Pylypjuk and Monárrez-Espino 33 found no association between a false-positive result for aneuploidy and FGR, but their study analyzed only maternal serum tests without a combined algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the potential usability of maternal biomarkers from fetal aneuploidy screening tests in predicting adverse pregnancy outcomes 16 , 17 . Particularly, one such biomarker estrogen produced in the placenta has been suggested to have a normal endocrine effect during pregnancy and maternal estrogen levels at delivery were found to be significantly and positively correlated with neonatal birth weight 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…A few reviews have attempted to summarize the risks associated with single serum marker aberrations or random combinations of markers, but due to the heterogeneity of these studies and their respective patient populations, the results are inconsistent [21][22][23]; variable cut-offs of individual serum markers or random combinations of markers also limit the clinical application of such fundings. Furthermore, many of the individual studies were small and underpowered to adequately assess risk for some of these rarer adverse pregnancy outcomes [9,[24][25][26]. Placentally mediated complications of pregnancy (preeclampsia, fetal growth restriction, preterm birth, and stillbirth) confer considerable risk for mothers and newborns worldwide.…”
Section: Introductionmentioning
confidence: 99%